Parent‐Adolescent Emotion Dynamics at Multiple Time Scales. (15th April 2021) - Lougheed, Jessica P.; Keskin, Gizem
Abstract: Developmental processes are embedded in social contexts, such as with family members. Adolescent development involves significant reorganization of the parent‐adolescent relationship, which is fundamental to the continued psychosocial development of both the adolescent and the parent. In this article, we introduce the model of parent‐adolescent dyads as temporal interpersonal emotion systems (TIES), which specifies the emotion‐related processes at multiple time scales that are implicated in the psychosocial development of both individuals. Building off our previous work, we outline study designs to examine development in parent‐adolescent TIES, which will lead to important new directions in research on developing adolescents and parents.